Predicting Outcomes in Critically Ill Canadian Octogenarians - Ball, Ian (Université d'Ottawa / University of Ottawa, 2016)
Background: Based on survey data from both Canada and abroad, most people would prefer to be cared for and to die in their own homes. Although 70% of elderly patients state a preference for comfort care over high technology life prolonging treatment in an inpatient setting, 54% are still admitted to intensive care units (ICUs). Understanding their wishes regarding end-of-life care, and being able to engage in evidence informed end-of-life discussions has never been so important, in order to empower patients, and to optimize scarce resource management. For the purpose of this thesis, “very old” patients will be defined as those eighty years of age and older. All three manuscripts will be based on data from the Realistic 80 study, a prospective cohort trial of 1671 critically ill very old patients admitted to 22 Canadian ICUs. Objectives: Manuscript 1: To describe the hospital outcomes of the entire cohort of Realistic 80 patients, including their ICU mortality and length of stay, their hospital mortality and length of stay, and their ultimate dispositions. Manuscript 2: To derive a clinical prediction rule for hospital mortality in the medical patient cohort. Manuscript 3: To derive a clinical prediction rule for hospital mortality in the emergency surgical patient cohort. Data Source: A prospective, multicenter cohort study of very elderly medical and surgical patients admitted to 22 Canadian academic and non-academic ICUs. Methods: Clinical decision rule methodology was used to analyze the data set and to create two separate clinical prediction tools, one for critically ill elderly medical patients, and one for critically ill surgical emergency patients. A third manuscript describing general clinical outcomes was also produced. Results of Manuscript 1: A total of 1671 patients were included in this section of the “Realities, Expectations and Attitudes to Life Support Technologies in Intensive Care for Octogenarians: The Realistic 80 Study (a prospective cohort of nearly 2000 critically ill Canadian patients over eighty years old enrolled from 22 ICUs across Canada) that will provide the data for this thesis. The Realistic 80 cohort had a mean age of 84.5, a baseline Apache II score of 22.4, a baseline SOFA score of 5.3, an overall ICU mortality of 21.8%, and an overall hospital mortality of 35%. The cohort had a median ICU length of stay of 3.7 days, and an overall median hospital length of stay of 16.6 days. Only 46.4% of the survivors were able to return home to live. Results of Manuscript 2: Age, renal function, level of consciousness, and serum pH were the important predictors of hospital mortality in critically ill elderly medical patients. Our clinical prediction tool is very good, particularly at the all-important extremes of prognosis, and ready for external validation. Results of Manuscript 3: Renal function and serum pH were the important predictors of hospital mortality in critically ill elderly surgical patients. Our model’s performance is very good, and will serve to inform clinical practice once validated. Conclusions: Very old medical patients have longer ICU stays and higher mortality than their surgical counterparts. Premorbid health status and severity of illness are associated with mortality. Our medical patient clinical prediction tool is very good and ready for external validation. Our surgical emergency clinical prediction tool shows promise, but will require the incorporation of more patients and a repeat derivation phase prior to external validation or clinical implementation.
Keywords: critical illness; intensive care unit; elderly; clinical decision rule; prognosis